Factors Related to the Nutritional Status of Toddlers at Palla Public Health Center - Bili, Maria Alfonsa Ina; Talahatu, Anna Henny; Ndoen, Honey Ivon (Timorese Journal of Public Health, 2022)
The state of the body known as nutritional status is the outcome of a balance between nutritional intake and needs. This study's objective was to determine how a mother's knowledge, occupation, and eating habits affected her kids' nutritional status while she worked at the Palla Health Center. The approach is an analytical survey using a cross-sectional study design. This study was conducted in the Palla Health Center from June to July 2021. Population in this study was mother of toddler who were between the ages of 1-3 years at Palla Publich Health Center and 68 samples were taken by accidental technique.The univariate and bivariate analyses that were carried out used the chi-square test with a significance threshold of = 0.05. The results showed that, while maternal education (p-value = 0.811), food expenditure (p-value = 0.100), and maternal compliance in bringing children to hygienic facilities were not related to toddlers' nutritional status, whereas mother’s knowledge (p-value = 0.035), mother's occupation (p-value = 0.000), consumption patterns (p-value = 0.004), and number of family members (p-value = 0.001)is related to nutritional status of toddler.mothers of toddler are urged to monitor their eating habits carefully because they will have a big impact on their nutritional state